Moonwalk with Your Eyes A Pocket Field Guide - Plotner, Tammy (Astronomer's Pocket Field Guide, 2010)
Are you ready to take a quarter of a million mile journey with just your eyes? Then welcome to "Moon Walk with Your Eyes"! We often take the beauty of our nearest astronomical neighbor for granted. How often do we really stop to think about why it looks the way it does or what a closer look will reveal? In this book, written in easy-to-understand language by one backyard astronomer to another, we'll explore the Moon night by night, as it goes through a full cycle. Every lunar day has something new to learn! And along your journey, you will be reading about the history, mystery, poetry, and legends that are associated with our Moon. Charts will help guide you to specific lunar features, as well as annotated photographic maps that pinpoint important or unusual craters. You'll soon learn to identify major features at just a glance and be able to create your own world-class images. You'll have right at hand the times and dates for every lunar day, phase, and eclipse for years to come. Imagine yourself at the telescope "crater hopping" to new challenges and being able to instantly identify Moon features. Picture yourself using binoculars and naming all you can see with ease! Within weeks, you'll be able to show everyone where each mission landed and tell amazing facts. So go ahead and Moonwalk with your eyes. Once you start your journey, you won't want to turn back!